Faktor Yang Mempengaruhi Kejadian Skabies Pada Santri Di Pondok Pesantren Hidayatullah Tanjung Morawa - Br Ginting, Heni Sry Wahyuni; Faried Lubis, Taufik Akbar; Nurfadly, Nurfadly; Syafrin Lubis, Riri Arisanty (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Scabies is a skin disease caused by infestation and sensitization to the hominis variant Sarcoptes scabei mite and its products.According to the Ministry of Health of the Republic of Indonesia, the prevalence of scabies in 2020 was 3.9%-6%.This states that Indonesia is still not free from scabies and is one of the infectious skin disease problems in Indonesia. The factors that cause the incidence of scabies to increase are high humidity, low sanitation, environmental density, poor personal hygiene, knowledge and attitudes and behaviors that are not supportive for a healthy lifestyle. The prevalence of scabies in Islamic boarding schools is still fairly high based on the results of the research conducted.This study aims to find out Factors Influencing the Occurrence of Scabies To students at Hidayatullah Islamic Boarding School Tanjung Morawa. cross seictional Observational analytics using a cross sectional design. Data were obtained through filling out questionnaires and physical examination of 94 samples then analyzed using univariate, bivariate analysis with the chi-square method and multivariate analysis will be carried out using multiple logistic regression tests to see the most dominant risk factors for Sarcoptes scabeii var infection. hominis. Data analysis using Chi Square showed that there was a relationship between Age and Personal hygiene Logistic regression analysis showed that the personal hygiene variable was the most dominant variable related to the event.